Pemanfaatan Whatsapp Group Pembelajaran Jarak Jauh dalam Meningkatkan Hasil Belajar Al Quran Siswa Kelas VI SD Bintang Bontang Tahun Pelajaran 2023/2024 - Mutiara, Tira; Ihsan, Muh. (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2025)
This research aims to determine the use of WhatsApp Groups as control tools in distance learning to improve Al learning outcomes Quran for class VI students at Bintang Bontang Elementary School for the 2023/2024 academic year. Study carried out using a descriptive qualitative approach. Subject The research consisted of teachers and sixth grade students who were involved in learning Al Quran via the Whatsapp platform. Data collection is carried out through observation, interviews and documentation. The research results show that The use of WhatsApp Group as a control tool can be effective in improve the quality and results of students' Al-Quran learning. This research giving the impact that technology can be an effective means for supporting religious learning, especially in the context of distance learning much more relevant today. The results of this study suggest so that schools and teachers are more active in using digital technology in their efforts improve the quality of Al-Quran learning and prepare students face future technological challenges. In conclusion, utilization Whatsapp Group improves students' Al Quran learning outcomes by supporting integration of technology in effective religious education.